Contributions of geology for the development of tourism in the region of Morro Redondo and Alta and Patrocínio Amaro waterfalls, Ipoema district, Itabira - MG (Research, Society and Development, 2017)
Tourism corresponds to an economic modality, which is related to the natural, geographic, cultural, historical and geological characteristics of a place, being this activity of great importance for the development and exploration of a certain region. In this context, the region of Ipoema, district of Itabira (MG), stands out for your natural attractions such as waterfalls and overlook, which attract tourists to the locality, as well as the Museum of Tropeiro, which displaying part of the history of Brazil. The objective of this work was to characterize the lithotypes and geological outcrops in the Morro Redondo region and the Alta and Patrocínio Amaro waterfalls, located in the district of Ipoema, Itabira/MG, identifying the potential of natural attractions for the development of different tourist modalities. Thus, quartzite rocks were observed in the region, with granulation ranging from thin to midsize, characterized by well developed, locally corrugated foliation planes, which can be correlated to the Sopa-Brumadinho Formation, basal sequence of the Espinhaço Supergroup. In general, the region has potential for the ecotourism development, adventure tourism and cultural tourism. Although the geology of the region does not favor the geotourism development, this should be considered for the tourist activity planning, since the weathering of quartzite rocks originates sandy soils that need adequate management and protection, thus avoiding the degradation of these areas.